IMPACT OF THE ORGANIZATIONAL CULTURE ON ORGANIZATIONAL LOYALTY (FIELD STUDY IN THE COLLEGE OF AL-KUNOOZ UNIVERSITY) - Abdulrazak Amer Adnan Alsadoon (Scholar Express Journals, 2022)
This paper determined to identify the impression of adaptation [organizational culture] on [organizational loyalty] and consider it a predictive variable (1) purpose, (2) ownership, (3) climate, (4) effective leadership, (5) university values, (6) openness, in all of its dimensions (1) organizational commitment (2) effective commitment (3) continuous commitment (4) normative commitment. The questionnaires distributed to the responsible specialists and staff at 87 samples served the study’s research. The statistical programmer [IBM SPSS] V. (22) was used to discover the (mean measurement), the [standard deviation] and the relative importance of the dimensions of the predictive variables [organizational culture]. The overall dimensions significantly affect the variables [organizational culture] on the [dependent] variable, university organizational loyalty in totality. The statistically [significant effect] on the variable’s dimensions: the [organizational culture (1) values (2) organization property (3) organizational climate], on the [dependent] variable, the [organizational loyalty] completely. This is the process by which [organizational culture] toward the memberships of the University, that common university values that help to understand, organize, develop and increase the performance of the education, leads to the commitment and dedication of the memberships of the further education college to all that contribute to the success of the University, as well as the goal of all that is not only to remain at the university but also that everyone is actively trying to find jobs in other fields at the [college or university] itself to complete their aims and thus develop and achieve the university's objectives.
Keywords: The Organizational Culture; Organizational Loyalty